Elevated Cr(VI) reduction in a biocathode microbial fuel cell without acclimatization inversion based on strain Corynebacterium vitaeruminis LZU47-1. (14th January 2021) - Zhao, Shuai; Chen, Zhengjun; Khan, Aman; Wang, Jicun; Kakade, Apurva; Kulshrestha, Saurabh; Liu, Pu; Li, Xiangkai
Abstract: Biocathode application in microbial fuel cell has been developed as a sustainable technology for heavy metal reduction. However, most biocathodes require pretreatment with acclimatization inversion. Here, a biocathode MFC based on strain Corynebacterium vitaeruminis LZU47-1 without acclimatization inversion was constructed for hexavalent chromium reduction. The maximum power generation by the biocathode MFC with C . vitaeruminis LZU47-1 increased by 24.5% and 53.4% in inversion and abiotic cathode groups, respectively. Compared with the inversion (72.52%) and abiotic cathode groups (64.75%), the biocathode group achieved a Cr(VI) removal efficiency of 98.63%. Furthermore, electrochemical analysis such as SEM-EDS, XPS and CV test were conducted to elucidate the adsorption-reduction mechanism for Cr(VI) reduction. MiSeq sequencing revealed that Geobacter (51.28%) was enriched on the anode biofilm in the biocathode group than inversion (38.52%) and abiotic cathode groups (31.74%). Therefore, this study provides a convenient and highly effective method for enhancing power output and Cr(VI) reduction in biocathode MFCs. Graphical abstract: Image 1 Highlights: A Cr(VI) reduction strain LZU47-1 can form biofilm in electrode for current output. A biocathode MFC was fabricated by strain LZU47-1 without acclimatization inversion. High Cr(VI) reduction (98.63%) and power generation (252.36 mW/m 2 ) were obtained. Simultaneous treatment of combined pollutants with organic matters and heavy metals.